It's Not Only About Selling; It's About Passing on Black Culture: A Study with Afro-Entrepreneurs in Espirito Santo-Brazil - Oliveira, Lorrara Silvya Imagawa; Amaro, Rubens Araújo; Souza, Susane Petinelli; Júnior, Roberto Rodrigues Souza (Archives of Business Research, 2023)
We seek to analyze how Afro-entrepreneurs from Espírito Santo undertake to understand some relationships between race and entrepreneurship. Methodologically, we used a descriptive qualitative approach. The data was produced together with six Afro-entrepreneurs living in Espírito Santo, based on participant observations and interviews. For data analysis, we used interpretative narrative analysis. The main research results show that Afro-entrepreneurs can be configured as social entrepreneurs, disseminate knowledge linked to their ancestry, encourage black pride and are preferred by their clients, who choose them for identification. Afro-entrepreneurship has become a space for valuing black workers, moving from a hard area to a black area in the theory of social spaces. From this study, it was possible to perceive the relevance of actions that promote the insertion and retention of black men and women in schools, universities and the job market.